2016
DOI: 10.1080/02640414.2016.1209306
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of maturation-related variation in adolescent boy athletes’ adaptations to short-term resistance training

Abstract: This meta-analysis investigated the maturation-related pattern of adaptations to resistance training in boy athletes. We included studies examining the effects of 4-16-week resistance training programmes in healthy boy athletes aged 10-18 years. Pooled estimates of effect size for change in strength across all studies (n = 19) were calculated using the inverse-variance random effects model for meta-analyses. Estimates were also calculated for groups based on likely biological maturity status ("before", "during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 74 publications
5
94
6
1
Order By: Relevance
“…Earlier work of our group already provided evidence that under the influence of maturation and superimposed mechanical loading the development of muscle morphology and function might precede adaptive and developmental processes at the tendon level in adolescent volleyball athletes (Mersmann et al, 2014, 2017). The results of a recent meta-analysis indicate an increase in the responsiveness of the neuromuscular system to mechanical loading early in adolescence (Moran et al, 2016), which is likely in part related to the muscle-anabolic effects of sex hormones (Vingren et al, 2010; Hansen and Kjaer, 2014). The effects of the rapid increase of circulating sex hormones on tendon plasticity during growth on the other hand are basically unknown (Hansen and Kjaer, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work of our group already provided evidence that under the influence of maturation and superimposed mechanical loading the development of muscle morphology and function might precede adaptive and developmental processes at the tendon level in adolescent volleyball athletes (Mersmann et al, 2014, 2017). The results of a recent meta-analysis indicate an increase in the responsiveness of the neuromuscular system to mechanical loading early in adolescence (Moran et al, 2016), which is likely in part related to the muscle-anabolic effects of sex hormones (Vingren et al, 2010; Hansen and Kjaer, 2014). The effects of the rapid increase of circulating sex hormones on tendon plasticity during growth on the other hand are basically unknown (Hansen and Kjaer, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, puberty is associated with profound changes of the musculoskeletal and endocrine system, which affect the plasticity of muscle and likely tendon as well. Estrogen and particularly testosterone increase the anabolic responsiveness of muscle to mechanical loading (Vingren et al, 2010; Hansen and Kjaer, 2014) and a recent meta-analysis provided evidence for an increase of muscle strength plasticity during and after peak height velocity (Moran et al, 2016). Youth athletes feature markedly greater muscle size compared to untrained adolescents, as demonstrated by Kanehisa et al (1995b, 2003) as well as Hoshikawa et al (2011), and, though it has not been demonstrated thus far experimentally, it is likely that changes in muscle architecture also contribute to training-induced gains in strength in adolescents (Aagaard et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Strength increases naturally throughout maturation and is underpinned by neural and muscular alterations . For those who want to maximize a youth's strength gain, resistance training is a potent method for enhancing strength . However, the magnitude of strength adaptations to resistance training can be dependent on maturation status, among other factors .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] For those who want to maximize a youth's strength gain, resistance training is a potent method for enhancing strength. 10 However, the magnitude of strength adaptations to resistance training can be dependent on maturation status, among other factors. 10 For example, strength adaptations are greater in boys during, and after, peak height velocity (PHV) than before PHV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation